The Dose and Time Dependent Effects of HGF on Myf-5, MyoD and miR-31 Expression in Quiescent Primary Human Myoblasts - Passerin d'Entreves, Niccolo (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.